Investigation of Managing Effective and Efficient Cell Phone Reverse Logistics - Zhou, Huiqiong (2010)
There are many factors influencing the sustainability of Closed-Loop Supply Chain (CLSC) operations in the cell phone industry. This research aims to identify theses factors which directly have a great impact on unused cell phone returns in order to provide a better understanding of implementing effective and efficient reverse logistics in the cell phone industry. In particular, the current situation of the cell phone reverse logistics in USA, Europe and China would be discussed. Data and information were collected through semi-structured interviews and questionnaire surveys, in order to anaylse the process flows in the supply chain. The key findings include the demonstration of the current situation of using cell phones in China and attitudes towards the management of the cell phone reverse logistics market. In addition, the constructive suggestions and suitable solutions for the Chinese government, manufacturers and other related stakeholders would be provided in this research. These are theoretical and practical supports for academics and companies to understand the handling of unused cell phones. Simultaneously, they assist companies in identifying and positioning themselves in the CLSC in order to define their direction for sustainable development in the long-term.